The Indian imagiNation : colonial and postcolonial literature and culture - Mandal, Somdatta (Creative Books, 2007)
Contributed papers presented at the conference organized by the Indian Association for Commonwealth Literature and Language Studies held at Visva-Bharati, Santinketan in Feb. 3-5, 2006.